Transformational Leadership in Islamic Boarding School Character Education Based on Teachers' Phenomenological Perspectives - Sulaiman Sulaiman; Dedy Achmad Kurniady; Udin Syaefudin Sa'ud; Nur Aedi; Eka Prihatin (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: This qualitative phenomenological study investigates transformational leadership practices in Islamic boarding schools (pesantren) through the lens of teachers' lived experiences. The research was conducted at Pesantren X with six experienced teachers serving as primary participants through purposive sampling. Data were collected via in-depth semi-structured interviews and analyzed using Braun and Clarke's six-phase thematic analysis with ATLAS.ti version 24 software. The study identifies four major themes: (1) Presence as Pedagogy, whereby leaders cultivate spiritual transformation through active participation in daily religious rituals and consistent physical supervision; (2) Accessible Authority, demonstrating how leaders balance traditional Islamic authority with democratic accessibility mechanisms; (3) Value Transmission Through Practical Responsibility, showing how students develop character virtues (amanah, integrity, and trustworthiness) through authentic management responsibilities; and (4) Restorative-Investigative Conflict Resolution, integrating Islamic justice principles (musyawarah and collective learning) with contemporary restorative practices. Findings reveal that transformational leadership in pesantren operates distinctly from Western organizational models, emphasizing relational presence, moral exemplarity, and communal value-formation. This study provides culturally-grounded empirical evidence enriching transformational leadership theory within Islamic educational contexts, offering actionable insights for pesantren administrators and informing educational policy development in Indonesian secondary education. Keywords: transformational leadership; Islamic boarding school; character education; pesantren; teacher perspectives